Implementation of Social Emotional Learning Approach of Senior High School Students of Gowa - Darmawati, Darmawati; Umar, Firman; Suyitno, Imam; Mustari, Mustari; Najamuddin, Najamuddin (CV. Eureka Murakabi Abadi, 2025)
This study aims to (1) Identify the implementation of the social emotional learning (PSE) approach at the curriculum level through the most relevant subjects; (2) Analyze the implementation of social emotional learning (PSE) in the school environment; and (3) Analyze the implementation of social emotional learning (PSE) in students. This study used a qualitative approach with a descriptive method. Data were obtained through interviews, observations and documentation with informants including teachers, staff, and students. The results of the study indicate that the implementation of PSE at SMAN 11 Gowa has covered three main aspects: (1) At the curriculum level, PSE is integrated into subjects such as Islamic Religious Education, Pancasila Education, and Indonesian, with learning methods that prioritize social and emotional values; (2) In the school environment, a positive, inclusive, and collaborative culture supports the social-emotional development of students; and (3) In students, teachers and staff have an important role in becoming role models and facilitators who support students' social and emotional competence. This study concludes that an integrated PSE approach that is integrated comprehensively in the curriculum, school environment, and learning community can improve the quality of learning while developing students' characters. This study provides an important contribution to the development of educational policies that support students' social and emotional skills.